THE EFFECTIVENESS OF THE USE OF BOARD GAME TOWARDS THE COMPREHENSION OF THE CONCEPT OF SOCIAL SCIENCE SUBJECTS (A Quasi Experimental Study in Eighth Grade of SMP Negeri 19 Bandung) - Fauziah, Ismi (International Journal Pedagogy of Social Studies, 2017)
Abstract-This research was inspired by the learning activity in Social Science subjects in SMPN 19 Bandung which was still teacher-centered. The Social Science subject itself is a subject which compact with the content starting from the real one to the one which requires abstract thinking, it makes the Social Science a subject which needs to be student centered, so that the students can be more active during the learning process and be able to arrange their own concept in their cognitive structure. This research was aimed to examine the effectiveness of the use of board game media towards studentâ€™s comprehension in the concept of social science subjects, using the quantitative approach. As for the research design used was a quasi experiment with the type of non-equivalent, pretest-posttest. The samples of this research were VIII-A class as the experimental class, was received treatment with the implementation of board game and VIII-B class as the control class, the one who did not receive the treatment. The data collection was carried out by using the objective tests and interviews which conducted to teachers and students in the experiment class.Â  After the data was collected, the next step was